ISOLASI DAN IDENTIFIKASI SENYAWA PENGHAMBAT POLIMERISASI HEM DARI FUNGSI ENDOFIT TANAMAN Artemisia annua L. - , Purwanto; , Prof. Dr. Wahyono, S.U., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Malaria is a life-threatening disease caused by Plasmodium parasites. The rapid spread of malaria-quinoline resistance enforce a finding of new antimalaria drug. Artemisia annua L plant that had artemisinin as secondary metabolic, had been used as antimalaria agent for long time ago. One source of bioactive compound is endophytic fungus. This fungus can produce the same or similar to its host plant. This research was done by isolation endophytic fungus, fermentation, extraction of fermentation medium and fungus miselium, analysis chromatogram with KLT, analysis of the haem polymerization inhibitory activity, analysis with HPLC and LC-MS, analysis of active compound group, and fungus identification. From 6 kind of fungus isolated from A. annua L., 3 kind of those fungus (fungus A, E, and F) was guessed could produce intracellular artemisinin. Fungus E had the highest value of the haem polymerization inhibitory activity with IC50 0,499 mg/mL. However, the analysis result of HPLC and LC-MS showed that fungus E did not contain artemisinin or its derivates, such dihydroartemisinin, arthemether, artheether, or artesunate. The result analysis of active compound group showed that fungus E miselium was consisted of terpenoid group compound, and this fungus was included in genus Tritirachium sp.